Economic conditions for sustainable development (Journal of Economic Research & Business Administration, 2025)
Sustainable development is a complex topic that can be analyzed from different perspectives. Key factors such as energy, population, food and economy have a significant impact on the mutual relationships between them. In the context of sustainable development, we distinguish the most important raw materials used for energy production, and those related to renewable energy sources. Although their global importance may be relatively small, they are crucial to achieving the goals of sustainable development. Disseminating information on this topic is essential to raise awareness and promote actions that promote ecological balance. The article focuses on the complexity of implementing the principles of sustainable development, which is a significant challenge in the context of global social and environmental changes. Analysis of data on population, energy and key issues of expenditure and production. The article indicates the interactions between these elements that can affect the effectiveness of actions for sustainable development.Keywords: sustainable development, energy, population.